2019
DOI: 10.1186/s41824-019-0061-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a novel 32-channel phased array for cardiovascular hybrid PET/MRI imaging: MRI performance

Abstract: Background: Cardiovascular imaging using hybrid positron emission tomography (PET) and magnetic resonance imaging (MRI) requires a radio frequency phased array resonator capable of high acceleration factors in order to achieve the shortest breath-holds while maintaining optimal MRI signal-to-noise ratio (SNR) and minimum PET photon attenuation. To our knowledge, the only two arrays used today for hybrid PET/MRI cardiovascular imaging are either incapable of achieving high acceleration or affect the PET photon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Although the novel array has 32 elements (almost 3 times more than the mMR 12ch), yet, we have shown that the novel array had better attenuation qualities that resulted in better PET images. The results from this study together with MRI performance of the same array reported in Farag et al (2019) suggest its suitability for PET/MRI cardiovascular imaging. This novel array can operate without needing AC for the anterior part, simplifying the attenuation correction while at the same time improving PET image quality.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Although the novel array has 32 elements (almost 3 times more than the mMR 12ch), yet, we have shown that the novel array had better attenuation qualities that resulted in better PET images. The results from this study together with MRI performance of the same array reported in Farag et al (2019) suggest its suitability for PET/MRI cardiovascular imaging. This novel array can operate without needing AC for the anterior part, simplifying the attenuation correction while at the same time improving PET image quality.…”
Section: Discussionsupporting
confidence: 60%
“…The no-array data was considered the frame of reference that each part of an array was compared to. Therefore, the RPD between no-array and each part of an array was estimated and reported using equation 4 as reported in (Farag et al, 2019) and presented here for convenience, where v 1 is the no-array case and v 2 is any given case (A, P, or A&P).…”
Section: Nac Datamentioning
confidence: 99%
See 1 more Smart Citation
“…We have selected an agreement threshold of ≤ 1% globally, aiming to improve attenuation accuracy over the CT-based AC method which is currently achieving (2.7%). After validating the technique, it was applied to the rigid/fixed posterior part of the 32-channel cardiac array described in [ 13 ] and the patient table.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, it would be preferable to use a receive array that is designed to have a low photon attenuation and avoid all aforementioned issues. A limited number of dedicated PET/MRI arrays have been developed (Dregely et al 2015, Sander et al 2015, Farag et al 2019 but dedicated arrays are not available for all systems, hence photon attenuating conventional arrays are used.…”
Section: Introductionmentioning
confidence: 99%